2021
DOI: 10.3390/molecules26164926
|View full text |Cite
|
Sign up to set email alerts
|

Solution/Ammonolysis Syntheses of Unsupported and Silica-Supported Copper(I) Nitride Nanostructures from Oxidic Precursors

Abstract: Herein we describe an alternative strategy to achieve the preparation of nanoscale Cu3N. Copper(II) oxide/hydroxide nanopowder precursors were successfully fabricated by solution methods. Ammonolysis of the oxidic precursors can be achieved essentially pseudomorphically to produce either unsupported or supported nanoparticles of the nitride. Hence, Cu3N particles with diverse morphologies were synthesized from oxygen-containing precursors in two-step processes combining solvothermal and solid−gas ammonolysis s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 70 publications
(65 reference statements)
0
5
0
Order By: Relevance
“…Nanomaterials 2022, 12, x FOR PEER REVIEW 6 of 25 particles [74]. Deshmukh et al synthesized Cu3N@SiO2 composites using a multistep approach [71].…”
Section: Gas-state Synthesis and The Ammonia Sourcementioning
confidence: 99%
See 3 more Smart Citations
“…Nanomaterials 2022, 12, x FOR PEER REVIEW 6 of 25 particles [74]. Deshmukh et al synthesized Cu3N@SiO2 composites using a multistep approach [71].…”
Section: Gas-state Synthesis and The Ammonia Sourcementioning
confidence: 99%
“…Multistep synthesis approaches have also been applied to the synthesis of Cu 3 N. These approaches are used to reduce copper oxide nanoparticles produced in the first step of the synthesis, followed by nitration. For example, Szczesny et al synthesized Cu 3 N nanoparticles with diverse morphologies from oxygen-containing precursors using a twostep process that combines solvothermal and solid-gas ammonolysis stages [74]. In the first step, copper (II) chloride dihydrate was used as a precursor for the fabrication of copper (II) oxide and copper (II) hydroxide nanoarchitectures by solvothermal methods.…”
Section: Solution-based Synthesismentioning
confidence: 99%
See 2 more Smart Citations
“…These methods involve the use of precursors such as Cu(hfac) 2 and [Cu(sBu-Me-amd)] 2 [21] to determine its resulting phase composition and morphology and to establish the growth rate [22,23]. Ammonolysis reactions can also be used to prepare bulk Cu 3 N powder samples [24], as well as thin films [25]. In addition, recent works have shown that Cu 3 N nanowire arrays can be synthesised by an ammonolysis reaction from copper (II) oxide precursors grown on copper surfaces deposited by electro or PVD in an ammonia solution [26,27].…”
Section: Introductionmentioning
confidence: 99%